Analysis of Contact Characteristic of Overhead Line and Suspension Clamp - Zhao Xinze; Zhao Meiyun; Peng Wei; Yang Zhicheng; Yang Zhenxing (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In this paper, a LGJ150/25 type ACSR transmission line and a CGU-3 type suspension clamp are taken as research objects. A contact model of the conductor and the clamp was established by using finite element method. The effects of sag angle of the conductor, holding force and tension force in section are analyzed. The results showed that the contact area in the middle of the clamp is of belt-like type. The extreme values of tress were observed on the edge of the contact area and near the edge of keeper. In clamp section, suspension angle had the greatest influence on contact stress, and then the clamp force. The tension force in section played a most important role in these affecting factors. In the exit section of clamp, the biggest impact factor was tension force in this section, then the suspension angle, the third was clamp force. The results provide theoretical basis on reducing corona loss, optimization the clamp. Doubtlessly, the conclusion has important theoretical significance and application value. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2227